Telemedicine for Mental Health: A Data-Driven Look at Effectiveness Studies - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The rapid expansion of telemedicine for mental health—often termed telemental health—has fundamentally reshaped the landscape of psychiatric and psychologica...
Keywords: Digital Health; Artificial Intelligence; Healthcare Innovation; Medical Ethics; Patient Care